THE EFFECT OF MOTIVATION ON THE ENTHUSIASM OF EDUCATORS IN DAYAH TAUTHIATUTH THULLAB ARONGAN, SIMPANG MAMPLAM DISTRICT, BIREUEN REGENCY, ACEH PROVINCE - Kamaruddin Kamaruddin; Mujidar Mujidar (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This research aimed to determine the effect of motivation on the Enthusiasm of educators in Dayah Tauthiatuth Thullab Arongan, Simpang Mamplam District, Bireuen Aceh Regency. The research method used in this study was correlational research designed to determine the level of relationship between different variables in a research subject. The purpose of this research was to determine how much influence or relationship between independent and dependent variables. The results showed that there was a positive and significant influence between motivation on the Enthusiasm of educators in Dayah Tauthiatuth Thullab Arongan, Simpang Mamplam District, Bireuen Aceh Regency and had a tendency to very good. In addition, the results of the research also showed that there was a positive influence, with a correlation value between X and Y of 64.8%. It was explained by variable X (100% - 23.7% - 76.3%) and by other reasons. In other words, the motivation which has an influence on the spirit of educators was 23.7%. And another factor that can affect the spirit of educators was 76.3%.